Fitness & Sportmedizin - Witassek C; Nitzsche N; Schulz H (Dynamic Media Sales Verlag, 2018)
The aim of the present study was to examine the effect of a jumping-fitness training on mini-trampolines on endurance capacity, trunk strength and reactive jump performance. 21 healthy, untrained volunteers were separated in an intervention group (n=12: age 224 years, BMI 22.62.6kg/m) and a control group (n=10: age 253 years, BMI 22.84.3kg/m). The participants in the intervention group completed an eightweek standardized jumping training on mini-trampolines with three training-sessions (TS) per week on average. The control group received no intervention. Pre- and posttests included a treadmill-test and a jumping-test to examine reactive jump performance (drop jump). Furthermore trunk strength was measured using an isometric maximum test. Additionally heart rate (HR), energy expenditure and perceived exertion (BORG 6-20) were monitored during all TS. After eight weeks of intervention jumping group showed significant increases in running speed at V4 and isometric maximum strength in trunk extension. Changes in jump performance were not significant (p>0.01). A nonsignificant group*time interaction was found (p>0.05). Control group showed no significant increase in all parameters (p>0.05). Participants of intervention group trained at 834% compared to their maximum heart rate. The mean energy expenditure was 9.72.5kcal/min during TS. The mean perceived exertion was 14.22.2 (somewhat hard/hard) and decreased over intervention period. The results show, that standardized jumping training on minitrampoline is a vigorous conditioning training and should be control on the effectiveness. KEY WORDS: Trampoline Exercise, Jumping, Endurance, Trunk Strength